Evidence for historic coastal high-energy wave impact (tsunami?) in North Wales, United Kingdom - Haslett, Simon; Bryant, Edward (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2007)
Understanding the contribution of high-energy events (e.g. storms, tsunami) to coastal evolution is currently much debated. Field investigations in North Wales on Anglesey and the Lleyn Peninsula have identified four sites where imbricated boulder trains occur that are discriminators of wave characteristics. Clast analysis indicates that storm wave heights (ca. 20 m), in excess of known extremes (5 to < 9 m), are required to transport them. A plausible explanation is the historic impact of tsunami (≥ 5 m high) that may have been caused either by a) a submarine slide situated offshore on the edge of the continental shelf or Rockall Trough, b) through seismic activity, as the region is one of the most seismically active regions of the British Isles, or c) impact of comet debris in the North Atlantic, with a candidate event around AD 1014. Field evidence suggests that such a high wave-energy event has not recurred along this coast within the last 400 years.